1985
DOI: 10.1111/j.1365-2605.1985.tb00817.x
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and dihydrotestosterone levels in the epididymis, vas deferens and preputial gland of mice during sexual maturation

Abstract: The levels of testosterone (T) and dihydrotestosterone (DHT) in the epididymis, vas deferens and preputial gland were assessed in mice from 1 to 90 days. The weight increase of these 3 organs was proportionately greater than that of the whole body until 50 or 60 days, and they attained their adult histological appearance approximately 20 days prior to puberty. Expressed in ng/g, the concentration of androgens (T+DHT) in the epididymis (14.3 to 36.5), vas deferens (6.6 to 24.0) and preputial gland (1.5 to 4.7) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 32 publications
(27 reference statements)
3
26
0
Order By: Relevance
“…The m5Kb-CAT gene expression was well correlated with the increase of DHT and androgen receptor content that occurs in the mouse epididymis during development (41,42). Castration, efferent duct ligation, and hormonal replacement studies confirmed that androgens, but not other testicular factors, were required to maintain m5Kb-CAT transgene expression in adult animals.…”
Section: -Kb Fragment Of Me-rabp Gene Drives Foreign Gene Expressionmentioning
confidence: 59%
“…The m5Kb-CAT gene expression was well correlated with the increase of DHT and androgen receptor content that occurs in the mouse epididymis during development (41,42). Castration, efferent duct ligation, and hormonal replacement studies confirmed that androgens, but not other testicular factors, were required to maintain m5Kb-CAT transgene expression in adult animals.…”
Section: -Kb Fragment Of Me-rabp Gene Drives Foreign Gene Expressionmentioning
confidence: 59%
“…However, the significant reduction in epididymal weight with GnRH-A treatment indicates its development as being androgen-dependent. This decline in epididymal weights may be due to elimination of transport of androgen binding protein (ABP) from testis to epididymis as a result of androgen withdrawal ( Jean-Faucher et al 1985, Danzo 1995. While estrogens increased SV size and fluid, they did not appear to antagonize epididymal developmental signal suggesting tissues with common embryologic origin may not share a common critical development period or development signal (Higgins et al 1981).…”
Section: Discussionmentioning
confidence: 98%
“…The principal cells become much more columnar, exhibit extensions of the Golgi apparatus, and have increased numbers of vesicles (51,52). The time frame between days 20 and 30 postpartum is also when there are increases in the levels of AR (53,54), testosterone, dihydrotestosterone (47,55), and the enzyme responsible for dihydrotestosterone production, 5-␣-reductase (56). Thus, the induction of Pem Pp transcription after day 20 could be the result of increased androgen and/or androgen responsiveness, which would also be consistent with our finding that region I is necessary for androgen-dependent transcription.…”
Section: Discussionmentioning
confidence: 99%